Implementasi Circular Economy Melalui Pengendalian Sampah Bahan Daur Ulang terhadap Peningkatan Pendapatan Masyarakat:: Studi Kasus Rumah Kompos dan Bank Sampah Induk Sicanang Kota Medan Provinsi Sumatera Utara - Ainun, Rofiqoh; Yusrizal, Yusrizal; Jannah, Nurul (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to find out, first, the planning process of the Sicanang Compost House and Garbage Bank for handling or managing waste in the community, second, the mechanism for implementing circular economy based waste management activities in increasing people's income, third, the constraints faced in implementing a circular economy through controlling recycled material waste and efforts to overcome it. This type of research uses descriptive qualitative research with data collection methods, namely observation, interviews, documentation and literature study. The results of the study concluded that first, in the planning process for tackling or managing waste based on a circular economy, the Main Sicanang Garbage Bank creates an annual program to provide an understanding to the community about the use-value of waste that will be realized. through the implementation of socialization activities and holding training and selling products, secondly, in carrying out circular economy based waste management activities to increase people's income, the Main Sicanang Garbage Bank has several stages of the mechanism, namely through the process of transporting waste, the process of sorting waste and up to the stage of the waste management process , thirdly, there are several obstacles encountered in implementing the circular economy through controlling recycled material waste, namely the operational part is large enough so that it cannot run the waste management program properly, then equipment and electricity are inadequate, and the mother's perception of unitary work communication about this institution. The Main Sicanang Induk Garbage Bank seeks to overcome community waste by processing organic and inorganic waste through a program that has been carried out and has succeeded in achieving 30%. Keywords: Circular Economy, Control of Recycled Material Waste, Community Income.